Oxidative stress and mitochondrial dysfunction of granulosa cells in polycystic ovarian syndrome - Gao, Yiyin; Zou, Yinggang; Wu, Guijie; Zheng, Lianwen (Frontiers in Medicine, 2023)
Polycystic ovarian syndrome (PCOS) is one of the leading causes of anovulatory infertility in women, affecting 5%–15% of women of reproductive age worldwide. The clinical manifestations of patients include ovulation disorders, amenorrhea, hirsutism, and obesity. Life-threatening diseases, such as endometrial cancer, type 2 diabetes, hyperlipidaemia, hypertension, and cardiovascular disease, can be distant complications of PCOS. PCOS has diverse etiologies and oxidative stress (OS) plays an important role. Mitochondria, as the core organelles of energy production, are the main source of reactive oxygen species (ROS). The process of follicular growth and development is extremely complex, and the granulosa cells (GCs) are inextricably linked to follicular development. The abnormal function of GCs may directly affect follicular development and alter many symptoms of PCOS. Significantly higher levels of OS markers and abnormal mitochondrial function in GCs have been found in patients with PCOS compared to healthy subjects, suggesting that increased OS is associated with PCOS progression. Therefore, the aim of this review was to summarize and discuss the findings suggesting that OS and mitochondrial dysfunction in GCs impair ovarian function and induce PCOS.